Robotic Harvest of a Rectus Abdominis Muscle Flap After Abdominoperineal Resection. Issue 9 (September 2020) - Hammond, Jacob B.; Howarth, Ashley L.; Haverland, Rachael A.; Rebecca, Alanna M.; Yi, Johnny; Bryant, Lyndsey A.; Polveroni, Thomas M.; Mishra, Nitin
Abstract : INTRODUCTION: As multidisciplinary treatment modalities for rectal cancer continue to evolve, neoadjuvant chemoradiation then surgical resection is a common approach. Robotic-assisted abdominoperineal resection is becoming more prevalent in part because of better visualization and instrument mobility within the pelvis. After abdominoperineal resection, postoperative perineal wound complications remain a significant risk. Pelvic reconstruction lowers this risk, and a pedicled rectus abdominis muscle flap is frequently used to achieve this. Traditional flap harvest requires laparotomy, resulting in violation of both rectus sheaths and a large midline scar. Robotic harvest of the rectus abdominis muscle for pelvic reconstruction after abdominoperineal resection is a novel approach with foreseeable benefits. TECHNIQUE: After completion of abdominoperineal resection, 2 additional trocars are inserted in the lateral abdomen, and the robot is reoriented toward the posterior abdominal wall. The peritoneum and posterior rectus sheath are incised, and dissection is carried superiorly and inferiorly in a sagittal plane to reveal the rectus abdominis muscle. The muscle body is separated from the anterior rectus sheath. Once the inferior epigastric artery is identified, the superior pole of the muscle is transected. Continued lateral dissection ensures flap mobility for placement within the pelvis. After obtaining proper reach, the robot is undocked, and the flap is sutured in place through the perineal defect. RESULTS: After trocar placement and robot repositioning, both the colorectal and plastic surgeons trade places at the console. Robotic flap harvest precludes the need for laparotomy. The anterior rectus sheath remains unviolated and the patient avoids an additional midline scar. The aforementioned benefits of robot-assisted abdominoperineal resection, namely increased visualization and maneuverability, were also found applicable when robotically harvesting this flap. CONCLUSIONS: This technique exemplifies an additional minimally invasive technique for patients pursuing abdominoperineal resection. With knowledge of this novel approach, surgeons can better tailor their operations to benefit the patient.